2023
DOI: 10.1108/jmlc-02-2023-0026
|View full text |Cite
|
Sign up to set email alerts
|

Does institutional quality modulate the effect of capital flight on economic growth in sub-Saharan Africa?

Abstract: Purpose Sub-Saharan African (SSA) region has been battling illegal outflow of capital over the years, with little success recorded so far. Without adequate attention, unemployment, infrastructure deficiencies and inefficient capital might be worse in the future. The purpose of this study is to investigate if institutional quality mitigates the effect of capital flight (CF) on economic growth. Design/methodology/approach The panel data from 26 SSA countries spanning 1998 to 2018 are used. The analysis of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 70 publications
(86 reference statements)
0
1
0
Order By: Relevance
“…The study revealed that institutional quality has a detrimental effect on economic growth, according to Akinlo (2023), a researcher who investigated the connections of institutional quality and economic growth in nations in Sub-Saharan Africa. Furthermore, Ogbuabor et al (2020) discovered that institutional quality specifically in West Africa has a detrimental effect on economic growth.…”
Section: Discussionmentioning
confidence: 99%
“…The study revealed that institutional quality has a detrimental effect on economic growth, according to Akinlo (2023), a researcher who investigated the connections of institutional quality and economic growth in nations in Sub-Saharan Africa. Furthermore, Ogbuabor et al (2020) discovered that institutional quality specifically in West Africa has a detrimental effect on economic growth.…”
Section: Discussionmentioning
confidence: 99%